Iglesia, Estado y política = Church, State and Politics - Castro Quiroga, Luis Augusto (Theologica Xaveriana, 2006)
Colombian situation includes the relation, at times a tense one, between Church, State and politics. Beyond the national fact, one must raise the question: how is this relation to be understood? The acting and thinking of Benedict XVI offers us an answer to it. The Church offers the service of ethical enlightenment to theState, which often, as the history of the twentieth century shows, is tempted to accept the lesser evil at the price of tolerating ethical transgressions. The Church, on the other side, must overcome the temptation of illicit silence in front of it and be faithful to its prophetical mission